Chemically modified water-soluble chitosan derivatives : Modification strategies, biological activities, and applications - Wan Roslina, Wan Yusof; Nur Yusra Farzana, Awang; Muhammad Affuwan Azhar, Laile; Juzaili, Azizi; Awang Ahmad Sallehin, Awang Husaini; Azman, Seeni; Lee D., Wilson; Sabar, Sumiyyah; Sumiyyah, Sabar (Taylor & Francis, 2023)
Chitosan, a biocompatible and nontoxic heteropolymer derived from chitin, offers various applications. However, its limited solubility above pH 6.5 hinders its broader applications. Chemical, physical, and enzymatic modifications have greatly improved chitosan properties, producing water-soluble chitosan (WSC) and derivatives. WSC and its derivatives possess unique structures, properties, and water solubility, meeting the demands of functional materials. This review highlights native chitosan characteristics, modification strategies for WSC and emphasizes its applications in food production, wastewater treatment, biomedical, and agriculture. Future perspectives for WSC and its derivatives are also discussed at the end of this paper.